PENGARUH MEDIA PEMBELAJARAN BERBASIS AUDIO VISUAL TERHADAP MINAT BELAJAR PESERTA DIDIK MATERI EKSRESI PADA MANUSIA DI SMAN 2 MEREUBO - Rufa hera; Rita Oktavia; Agus Kistian (LPPM Universitas Cipta Mandiri, 2024)
Biology is a science that generally contains abstract studies. The concept of biology urgently needs significant and interesting teaching media to encourage students to study biology comprehensively and in-depth. Currently, the use of learning media in the study of biological sciences has not been maximized by educators in schools, especially audiovisual-based media. The purpose of this study is to find out